(3cJGH GdYLGFHs - (3Pj Gdfhf GdeUQjs
(3ChdgG (B:s
(3bGd Ph Gdfhf GdENejei QMeg Gddg CdaJ cJGHi gPG hSejJg cJGH GdYLGFH hVefJ GdLRA GdChd efg LejY eG LQHJg aUM s
(3BNQgG (B:s
(3hQHWJ GdNQbI HNjW hhSYJ GdQHW YdjgG hYdbJ Ydi ef jTJci Yjfjfg hjYdb Ydi YVOg Ch ai Yfbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdMQha h GdChaGbs